Correlation of hemoglobin with osteoporosis in elderly Chinese population: A cross-sectional study - Yichen Liu; Yichen Liu; Yue Zeng; Yue Zeng; Jun Lu; Xiaoya Zhang; Xiaoya Zhang; Zikai Zhang; Huijuan Li; Huijuan Li; Peipei Liu; Bin Ma; et al. (Frontiers Media S.A., 2023)
IntroductionIn the elder population, both low hemoglobin (Hb)/anemia and osteoporosis (OP) are highly prevalent. However, the relationship between Hb and OP is still poorly understood. This study was to evaluate the correlation between Hb and OP in Chinese elderly population.MethodsOne thousand and sisty-eight individuals aged 55-85 years were enrolled into this cross-sectional study during June 2019-November 2019. Data on the demographics and clinical characteristics were recorded. Detections of complete blood count, liver/kidney function, glucose metabolism and lipid profile, and thoracolumbar X-ray were performed, and bone mineral density (BMD) at lumbar spine 1-4, femur neck, and total hip was measured by dual-energy X-ray absorptiometry (DXA). Univariate and multivariate linear regression analyses were employed to evaluate the correlation between Hb with BMD T-score. Logistic regression analysis was performed to access the correlation between different Hb levels and the odds ratio (OR) for OP.ResultsCompared with non-OP group, OP patients had lower level of Hb. Univariate linear regression analysis indicated Hb level was positively related to the BMD of lumbar spine 1-4, femur neck and total hip, and this relationship remained after adjusting confounding variables [gender, age, body mass index (BMI), diabetes mellitus (DM) and morphological vertebral fracture]. Logistic regression analysis showed the ORs for OP decreased with the increase of Hb. Compared with the subjects with the lowest quartile of Hb, the OR for OP in the highest quartile group was 0.60 (0.41-0.89) after adjusting for gender, age and BMI, and the OR for OP was 0.62 (0.41-0.92) after further adjustment for gender, age, BMI, DM, and lipid indexes.DiscussionIn conclusion, Lower Hb level is related to lower BMD in the elderly population. However, whether Hb level could be used to predict the risk of OP needs to be further determined in more longitudinal clinical studies.